2008
DOI: 10.1080/15421400701833973
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic Mesomorphism in Salen-like Zinc Complexes

Abstract: The reaction between a series of non mesogenic tetradentate salen-like Schiff bases and Zn(II) acetate gives rise to the formation of liquid cristalline complexes showing nematic and smectic phases stable over a quite large temperature range. A dimeric structural arrangement could favour the appearance of such type of mesophase in the case of 1,3-diaminopropane and 1,3-diamino-2,2-dimethylpropane bridges containing ligands while for the salen derivatives a monomeric solvent-induced pentacoordinated arrengement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 17 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…This complex exhibits low transition temperatures in comparison with the title complexes of this work and undergo decomposition near the transition to the isotropic liquid. Finally, Aiello et al [30] reported a new type of zinc(II) complexes derived from tetradentate salen-like Schiff-base ligands containing …”
Section: Synthesis and Liquid-crystalline Properties Of Nickel(ii) Comentioning
confidence: 98%
See 1 more Smart Citation
“…This complex exhibits low transition temperatures in comparison with the title complexes of this work and undergo decomposition near the transition to the isotropic liquid. Finally, Aiello et al [30] reported a new type of zinc(II) complexes derived from tetradentate salen-like Schiff-base ligands containing …”
Section: Synthesis and Liquid-crystalline Properties Of Nickel(ii) Comentioning
confidence: 98%
“…These complexes show nematic and smectic C(S m C) mesophases [30]. However, the complexes described in this work are more thermally stable than those based on ethylene and trimethylene bridges.…”
mentioning
confidence: 94%